2017
DOI: 10.3390/healthcare5030030
|View full text |Cite
|
Sign up to set email alerts
|

Progestin Intrauterine Devices and Metformin: Endometrial Hyperplasia and Early Stage Endometrial Cancer Medical Management

Abstract: Globally, endometrial cancer is the sixth leading cause of female cancer-related deaths. Non-atypical endometrial hyperplasia (EH), has a lifetime progression rate to endometrial cancer ranging from less than 5%, if simple without atypia, to 40%, if complex with atypia. Site specific, long-acting intrauterine devices (IUDs) provide fertility sparing, progestin-based EH medical management. It is unclear which IUD is most beneficial, or if progesterone sensitizing metformin offers improved outcomes. For resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been well established that metformin restrains EH via mTOR pathway modulation [ 110 ], as it activates AMPK, a significant negative regulator of mTOR signaling [ 111 ]. In PCOS, metformin can increase GLUT-4 and reduce androgen receptor (AR) levels in the endometrium, probably through the mTOR pathway [ 106 , 112 ].…”
Section: Mtor and Eif Signaling In Benign Endometrial Diseasesmentioning
confidence: 99%
“…It has been well established that metformin restrains EH via mTOR pathway modulation [ 110 ], as it activates AMPK, a significant negative regulator of mTOR signaling [ 111 ]. In PCOS, metformin can increase GLUT-4 and reduce androgen receptor (AR) levels in the endometrium, probably through the mTOR pathway [ 106 , 112 ].…”
Section: Mtor and Eif Signaling In Benign Endometrial Diseasesmentioning
confidence: 99%
“…In addition, for some patients with EC, surgical treatment appears to be unsuitable because of morbid obesity and other serious complications. Recently, several studies on the non-surgical treatment of EC have revealed new insights into this malignancy (12,13). Progestin and metformin are promising candidates as therapeutic agents for EC treatment (14).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-mediating effects of metformin have shown evidence of reducing the incidence of malignancies and improving patient survival ( 12 , 35 , 38 ). In addition, metformin has the potential to increase progestin-driven anti-proliferative mechanisms ( 39 ).…”
Section: Discussionmentioning
confidence: 99%